Research on the Mechanism of Cognitive Decline in Patients With Acoustic Neuroma - Deng, Xueyun; Liu, Lizhen; Luo, Jun; Liu, Lihua; Hui, Xuhui; Feng, Hua (Frontiers in Neuroscience, 2022)
Little is known about neuropsychological research on patients with acoustic neuroma (AN), especially cognitive neuropsychology. We aim to compare the cognitive function between AN patients and healthy controls and explore possible underlying mechanisms. Various neuropsychological assessments were performed on all participants. Tract-based spatial statistics (TBSS) was used to compare DTI metrics such as fractional anisotropy (FA), axial diffusivity (AD), radial diffusivity (RD), and mean diffusivity (MD). Correlation analysis was analyzed between DTI metrics and cognitive scales. Compared with the HC group, the AN group performed worse in the neuropsychological evaluations, and TBSS analysis showed widespread alteration of the FA, AD, RD, and MD, which correlated with the cognitive function. These white matter tracts include minor forceps, major forceps, anterior thalamic radiation, superior longitudinal fasciculus, corticospinal tract, and right inferior fronto-occipital fasciculus. Meanwhile, we found for the first time that cognitive decline was related to the decrease of FA in minor forceps, which can be used as a neurobiological marker of cognitive impairment in AN patients. The occurrence of cognition impairment is common in AN patients. Including neuropsychological evaluation in the routine clinical assessment and appropriate treatment may strengthen clinical management and improve quality of life of patients.